Bilitranslocase and sulfobromophthalein/bilirubin-binding protein are both involved in the hepatic uptake of organic anions. - Torres, A M (1993)
The hepatic uptake of cholephilic organic anions is a carrier-mediated process. Three distinct proteins [bilitranslocase (BTL), sulfobromophthalein (BSP)/bilirubin-binding protein (BBBP), and organic anion-binding protein] have been isolated from the basolateral plasma-membrane domain of the hepatocyte. To investigate the relative role of the first two of them in accounting for the hepatic uptake of organic anions, we measured the initial rates of uptake of 35S-labeled BSP into rat liver plasma-membrane vesicles. Because transport by BTL is electrogenic but transport by BBBP is electroneutral, studies were done either with or without a positive-inside membrane potential produced by adding valinomycin in the presence of an inwardly directed K+ gradient (outside K+ > inside K+). Both electrogenic and electroneutral transport systems followed saturation kinetics. Electroneutral uptake showed an apparent Km of 20 +/- 3 microM (mean +/- SD) and a Vmax of 1.0 +/- 0.13 nmol.(mg of prot)-1.15 sec-1, whereas the electrogenic portion of BSP uptake exhibited a Km of 5.2 +/- 0.8 microM and a Vmax of 1.1 +/- 0.1 nmol.(mg of prot)-1.15 sec-1. In this case, an overshoot was observed 15 sec after valinomycin addition. Electroneutral BSP uptake was inhibited by incubation with anti-BBBP antibody, whereas anti-BTL antibody did not show any inhibitory effect. Conversely, the electrogenic uptake was inhibited by anti-BTL antibody at a BSP concentration of 5 microM; no inhibition was seen either at 20 microM BSP or upon addition of anti-BBBP antibody. From these data we conclude that the hepatic uptake of organic ions occurs via two immunologically distinct carrier proteins (BTL and BBBP) operating in parallel. BTL is a higher affinity electrogenic transporting system of organic ions, whereas BBBP is a lower affinity electroneutral transporter.